2016
DOI: 10.4049/jimmunol.1600799
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lamprey BAFF-like Gene: Evolutionary Implications

Abstract: BAFF (TNFSF13B/Blys) and APRIL (TNFSF13), are important regulatory factors for lymphocyte activation and survival in mammals. A BAFF/APRIL-like relative called BALM has also been identified in cartilaginous and bony fishes, and we report here a BAFF-like gene in lampreys. Our phylogenetic analysis of these genes, and a related TNFSF12 gene called TWEAK, suggest that, whereas an ancestral homologue of BAFF and APRIL was already present in a common ancestor of jawed and jawless vertebrates, TWEAK evolved early o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 70 publications
(65 reference statements)
4
38
1
Order By: Relevance
“…This study also determined that BALM gene was mainly expressed in lymphoid tissues. In a more recent study, BALM orthologs have been found in cartilaginous fish ( 168 ) (Table 3 ), in addition to a BAFF-like sequence showing homology to BAFF, APRIL and BALM present in lampreys ( 168 ). In this study, the authors described that BALM is absent in all tetrapods, and there is a selective deletion of this gene in zebrafish.…”
Section: Baff- and April-like Molecule (Balm)mentioning
confidence: 95%
See 1 more Smart Citation
“…This study also determined that BALM gene was mainly expressed in lymphoid tissues. In a more recent study, BALM orthologs have been found in cartilaginous fish ( 168 ) (Table 3 ), in addition to a BAFF-like sequence showing homology to BAFF, APRIL and BALM present in lampreys ( 168 ). In this study, the authors described that BALM is absent in all tetrapods, and there is a selective deletion of this gene in zebrafish.…”
Section: Baff- and April-like Molecule (Balm)mentioning
confidence: 95%
“…In fact, although BAFF homologs have been identified in many cartilaginous and bony fish (summarized in Table 3 ), only a few APRIL homologue sequences have been found in teleost, specifically in zebrafish, channel catfish, Atlantic salmon, rainbow trout ( 41 ), and grass carp ( 134 ) (Table 3 ). In addition, while BAFF is present in all vertebrates, APRIL is missing in cartilaginous fish, birds, and several bony fish ( 168 ). This has encouraged evolutionary immunologists to hypothesize that since BAFF and APRIL have structural and functional similarities and share receptors, the absence of APRIL on cartilaginous fish or the loss of APRIL in avian species could have been functionally compensated by BAFF.…”
Section: A Proliferation-inducing Ligandmentioning
confidence: 99%
“…( 17 )], only a few APRIL homolog sequences have been found in teleost, specifically in zebrafish ( Danio rerio ) ( 18 , 19 ), channel catfish ( Ictalurus punctatus ) ( 18 ), Atlantic salmon ( Salmo salar ) ( 18 ), rainbow trout ( Oncorhynchus mykiss ) ( 18 ), and grass carp ( Ctenopharyngodon idella ) ( 20 ). Interestingly, while BAFF is present in all vertebrates, APRIL is missing in cartilaginous fish, birds and several bony fish, suggesting that in some animal groups BAFF might have functionally compensated the loss of APRIL ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Animals were sacrificed in 0.01% MS-222 followed by exsanguination. Adult lamprey blood was collected by cutting the tail, and leukocytes were separated by Ficoll-Paque gradient centrifugation of the blood with lymphocyte separating solution (160 × g, 20 min) (27)(28)(29). Subsequently, the lamprey lymphocytes were collected for the following studies.…”
Section: Animal Maintenancementioning
confidence: 99%
“…qPCR was performed in triplicate using a TaKaRa PCR Thermal Cycler Dice Real Time System, and L-gapdh (GenBank accession No. KU041137.1) was used as an internal control (28,29,34). The reaction efficiency was tested by the gradual dilution of cDNA template (1x, 5x, 10x, 20x, and 40x).…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%